2007
DOI: 10.3390/12061220
|View full text |Cite
|
Sign up to set email alerts
|

Solar Ultraviolet-B Radiation Increases Phenolic Content and Ferric Reducing Antioxidant Power in Avena sativa

Abstract: Abstract:We examined the influence of solar ultraviolet-B radiation (UV-B; 280-320 nm) on the maximum photochemical efficiency of photosystem II (F v /F m ), bulk-soluble phenolic concentrations, ferric-reducing antioxidant power (FRAP) and growth of Avena sativa. Treatments involved placing filters on frames over potted plants that reduced levels of biologically effective UV-B by either 71% (reduced UV-B) or by 19% (near-ambient UV-B) over the 52 day experiment (04 July -25 August 2002). Plants growing under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 60 publications
(71 reference statements)
1
20
0
1
Order By: Relevance
“…Some stresses, such as ultraviolet B (UV-B) light, can cause an increase in the levels of phenolic compounds, which protect plants against injury and function as an antioxidant system [32]. This is congruent with the observation that treatment of wax apple with PGRs resulted in higher PAL and antioxidant activity levels and that specific combinations of GA3, NAA, and 2, 4-D are positively correlated with increases in the levels of phenolic compounds and flavonoids [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some stresses, such as ultraviolet B (UV-B) light, can cause an increase in the levels of phenolic compounds, which protect plants against injury and function as an antioxidant system [32]. This is congruent with the observation that treatment of wax apple with PGRs resulted in higher PAL and antioxidant activity levels and that specific combinations of GA3, NAA, and 2, 4-D are positively correlated with increases in the levels of phenolic compounds and flavonoids [19].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced levels of UV radiation have been shown to affect plant chemical composition by promoting an array of protective responses in plants including the production of UV absorbing compounds known as phenolics and other antioxidants. Ruhland et al, (2007) observed that concentrations of bulk-soluble phenolics and ferric reducing antioxidant power (FRAP) were 17% and 24% higher under nearambient UV-B than under a 71% reduction in UV-B, respectively. Furthermore, Rousseaux et al, (2004) observed that, in oat and lettuce, UV-absorbing compounds responded more to supplemental UV-B radiation (simulating a 30% decrease in ozone) when compared to ambient solar UV-B radiation suggesting elevated UV-B radiation may accelerate changes in plant chemistry.…”
Section: Plant Chemistrymentioning
confidence: 97%
“…It is well documented that the chemical composition of plants is altered under UV exposure due to changes in nutrient content and tissue composition (Rozema et al, 1997). Corresponding alterations in plant litter quality indirectly inhibit carbon release by reducing the rate at which microbial communities can access biologically important molecules during the decomposition process (Mazza et al, 1999(Mazza et al, , 2000Rousseaux et al, 2004;Milchunas et al, 2004;Pancotto et al, 2005;Ruhland et al, 2007). Furthermore, exposure to UV radiation can also have a selective influence on the species composition of microbial communities resulting in further reduction in carbon release (Gehrke et al, 1995;Moody et al, 2001;Pancotto et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…En las plantas se han observado cambios fisiológicos, bioquímicos, morfológicos y anatómicos, afectando el crecimiento vegetal (Diffey, 1991), como por ejemplo en avena (Ruhland et al, 2007). Pero también se observan efectos significativos sobre la herbivoría por insectos (Ballare et al, 1996;Caputo et al, 2006), afectando además, al próximo nivel trófico (depredadores) (Foggo et al, 2007).…”
Section: Fecha Deunclassified